2009
DOI: 10.1002/pmic.200800667
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis of distinct tumor cell lines in response to nocodazole treatment

Abstract: Here, we report for the first time a comparative phosphoproteomic analysis of distinct tumor cell lines in the presence or absence of the microtubule-interfering agent nocodazole. In total, 1525 phosphorylation sites assigned to 726 phosphoproteins were identified using LC-MS-based technology following phosphopeptide enrichment. Analysis of the amino acid composition surrounding the identified in vivo phosphorylation sites revealed that they could be classified into two motif groups: pSer-Pro and pSer-Asp/Glu.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…2A). Similar results were obtained upon reprobing with 32 P-labeled DNA oligonucleotide specific to arginyl tRNA and glutamyl tRNA (data not shown). Electrophoresis of tRNA samples from non-synchronized and mitotic cells under acidic conditions, which preserve aminoacylation, ruled out possible differences in the overall levels of charged aa-tRNA in mitotic cells (Fig.…”
Section: Resultssupporting
confidence: 73%
“…2A). Similar results were obtained upon reprobing with 32 P-labeled DNA oligonucleotide specific to arginyl tRNA and glutamyl tRNA (data not shown). Electrophoresis of tRNA samples from non-synchronized and mitotic cells under acidic conditions, which preserve aminoacylation, ruled out possible differences in the overall levels of charged aa-tRNA in mitotic cells (Fig.…”
Section: Resultssupporting
confidence: 73%
“…This comprehensive study did not identify any phosphopeptides in eIF4GI, although an earlier independent study 42 did find phosphorylation of this paralog at both known sites (Ser 1186 and Ser 1188), together with another at Ser 1232. All these sites reside in the C-FAG fragment of eIF4GI and again could reflect the alteration in intensity of the 2 bands observed in Figure 5B, comparing lanes 5 and 6.…”
Section: Discussionmentioning
confidence: 79%
“…More proteins were modulated by MMAF-Ome, 5T4-ADC, or PF-384 alone, with only some showing cooperative effects by combined treatment with 5T4-ADC/ PF-384 or MMAF-OMe/PF-384. This comports with other largescale phosphoproteomic studies that identified a number of initiation factors differentially phosphorylated in response to the nocodazole treatment (32,33). Whereas targeting of translational components by auristatin-based agents is a novel finding, the effects of PF-384 are quite expected, given the known role of PI3K and mTOR kinases in the control of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%